Difficulty Achieving Vitamin D Sufficiency With High-Dose Oral Repletion Therapy in Infants With Cholestasis. Issue 2 (August 2015) - Jensen, Melissa; Abu-El-Haija, Maisam; Bishop, Warren; Rahhal, Riad M.
ABSTRACT: Objectives: Oral high-dose repletion vitamin D therapy, also known as stoss therapy, can be effective in the treatment of nutritional vitamin D deficiency rickets in infants and young children without liver disease and in patients with cystic fibrosis. There is no literature about this approach in infants with new-onset cholestasis. Methods: This was a retrospective chart review of infants with cholestasis from March 2010 to March 2012 at a pediatric tertiary care center. Four cases satisfied the inclusion criteria, and were described in detail. Results: All of the patients received oral high-dose repletion therapy with ergocalciferol (vitamin D2 ) 300, 000 IU daily for 2 to 3 days. Follow-up vitamin D levels approximately 4 weeks later showed failure to achieve sufficiency levels (>20 ng/dL) in any patient. Conclusions: Unlike infants without liver disease, use of oral high-dose repletion therapy may not be adequate as treatment of vitamin D deficiency in the setting of cholestasis.